PENGARUH DISIPLIN KERJA DAN KOMPENSASI TERHADAP KINERJA GURU DENGAN MOTIVASI SEBAGAI VARIABEL INTERVENING (STUDI PADA SD ISLAM AL AZHAR 35 SURABAYA) - Susantyo, Idham Faiz; Iryanti, Endang (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to analyze the impact of work discipline and motivation as an intervening variable on the performance of teachers at the Islamic Grundschule Al Azhar 35 in Surabaya. The study employs a quantitative research approach using data obtained using the fragebögen of forty respondents using a standard stitch-proben procedure. The collected data was then analyzed using the software Smart PLS. The study's findings demonstrate that both work discipline and compensation have a positive and significant impact on performance, that work discipline has a positive and significant impact on performance through motivation, and that compensation has no effect on performance throught motivation.